Significant potential of melatonin therapy in Parkinson’s disease – a meta-analysis of randomized controlled trials - Iftikhar, Sadaf; Sameer, Hafiz Muhammad; Zainab, (Frontiers in Neurology, 2023)
Objective: Since its discovery as an antioxidant, melatonin has been increasingly recognized for its therapeutic potential beyond sleep disturbances in neurodegenerative disorders. This study aims to evaluate efficacy of various melatonin doses, treatment durations, and formulations, in alleviating motor symptoms and sleep disturbances in Parkinson's disease, the second most common neurodegenerative disorder worldwide. Methods: PubMed, Cochrane Library, ClinicalTrials.gov and other databases were systematically searched to retrieve randomized controlled trials (RCTs) administrating melatonin to Parkinson's disease patients until June 10th, 2023. Outcomes including Unified Parkinson Disease Rating Scale (UPDRS) scores and Pittsburgh Sleep Quality Index (PSQI) scores, were pooled and reported as mean differences (MD) with 95% confidence intervals (CIs). Metaanalysis was performed using an inverse variance random-effects model in Review Manager 5.4 software. Trial Sequential Analysis was performed to avoid false-positive results from random errors. Results: Five RCTs with a total of 155 patients were included. Statistically significant reductions in UPDRS total scores were observed in groups receiving Melatonin ≥10 mg/day (MD=-11.35, 95% CI: -22.35 to -0.35, I2=0%, P=0.04) and immediate release formulations I2=0%, P=0.04). No significant effects on individual UPDRS II, III, and IV scores were observed, regardless of melatonin dosage and treatment duration. Moreover, significant improvements in PSQI scores were observed with only immediate-release melatonin formulations (MD=-2.86, 95% CI: -4.74 to -0.97, I2=0%, P=0.003). Conclusion: Melatonin ≥10 mg/day for a minimum duration of ≥12 weeks in immediate-release formulations consistently demonstrated significant therapeutic potential in improving motor symptom and sleep disturbances in Parkinson disease. However, further trials are warranted to investigate its impact when initiated early in the disease course to fully explore its true therapeutic potential.